Stimulation of cannabinoid receptors by using Rubus coreanus extracts to control osteoporosis in aged male rats. (June 2015) - Lim, Hae-Kyoung; Lee, Hye-Rim; Do, Sun Hee
Abstract A substantial proportion of men with prostatic disease have an increased risk of bone loss. In the present study, we investigated the effects of Rubus coreanus Miquel (RCM) extracts on osteoporosis that occurs with N-methyl-N-nitrosourea (MNU)-induced prostatic hyperplasia. The rats used in this study were categorized into groups of healthy controls, rats treated with MNU, and rats treated with MNU and RCM. The rats were sacrificed after 10 weeks of RCM treatment, after which ultrasonography, serum biochemical tests, histopathological examinations, immunohistochemical analysis, and semi-quantitative reverse-transcription polymerase chain reaction analysis were performed. There were no marked differences in body weight gain and the size and weight of the prostate gland between the MNU group and the MNU and RCM group. However, treatment with RCM inhibited osteoclastic osteolysis and reduced dysplastic progress in the prostate gland, as observed by histopathological evaluation and by analyzing changes in the levels of bone regulatory factors. In addition, the group treated with MNU and RCM had higher expression levels of cannabinoid receptors-1, -2, and osteoprotegerin. These results indicate that the anti-osteoporotic effect of RCM in prostatic hyperplasia is attributable to the cannabinoid receptor-related upregulation of osteoblastogenesis and inhibition of prostatic hyperplasia. The results of the present study suggest that treatment with RCM may benefit osteoporotic patients with prostatic disease by simultaneously altering the activation of osteoblasts and osteoclasts.